Toosendanin suppresses African swine fever virus replication through upregulating interferon regulatory factor 1 in porcine alveolar macrophage cultures - Yuanjia Liu; Xinheng Zhang; Zexin Liu; Li Huang; Weixin Jia; Xinlei Lian; Changjiang Weng; Guihong Zhang; Wenbao Qi; Jianxin Chen (Frontiers in Microbiology, 2022)
African swine fever virus (ASFV) is a highly infectious and lethal swine pathogen that causes severe socio-economic consequences in affected countries. Unfortunately, effective vaccine for combating ASF is unavailable so far, and the prevention and control strategies for ASFV are still very limited. Toosendanin (TSN), a triterpenoid saponin extracted from the medicinal herb Melia toosendan Sieb. Et Zucc, has been demonstrated to possess analgesic, anti-inflammatory, anti-botulism and anti-microbial activities, and was used clinically as an anthelmintic, while the antiviral effect of TSN on ASFV has not been reported. In this study, we revealed that TSN exhibited a potent inhibitory effect on ASFV GZ201801-38 strain in porcine alveolar macrophages (PAMs; EC50 = 0.085 μM, SI = 365) in a dose-dependent manner. TSN showed robust antiviral activity in different doses of ASFV infection and reduced the transcription and translation levels of ASFV p30 protein, viral genomic DNA quantity as well as viral titer at 24 and 48 h post-infection. In addition, TSN did not affect virion attachment and release but intervened in its internalization in PAMs. Further investigations disclosed that TSN played its antiviral role by upregulating the host IFN-stimulated gene (ISG) IRF1 rather than by directly inactivating the virus particles. Overall, our results suggest that TSN is an effective antiviral agent against ASFV replication in vitro and may have the potential for clinical use.